Incidence of Primary Aldosteronism in Patients with Hypokalemia (IPAHK+): Study Design and Baseline Characteristics - Gruber, Sven; Stasi, Evangelia; Steiner, Regula; Reincke, Martin; Bornstein, Stefan; Beuschlein, Felix (Hormone and Metabolic Research, 2021)
Hypokalemia plays a central role for case finding, course, treatment decision, and prognosis of patients with primary aldosteronism. However, to date there is a lack of high-level evidence about the incidence of primary aldosteronism in hypokalemic patients. The IPAHK+study is an epidemiological, cross-sectional, monocentric study to provide evidence on the incidence of PA in a hypokalemic population. The aim of the current analysis was to describe the baseline characteristics of the first 100 patients eligible for study inclusion. The recruitment of patients with hypokalemia (≤3 mmol/l) is carried out continuously on a referral-basis by the central laboratory of the University Hospital Zurich through an automated suitability testing and data delivery system. The careful evaluation of the first 100 reported patients was based on the available reporting system. Out of 28 140 screened patients, 222 (0.79%) were identified with a serum potassium value of≤3 mmol/l (mean 2.89±0.02 mmol/l). Mean potassium levels were slightly lower in non-hypertensive subjects compared to hypertensive subjects (mean difference 0.07 mmol/l, p=0.033), while no significant difference was found between the sexes and patients with and without the diagnosis of primary aldosteronism, atrial fibrillation, or the use of diuretics. The incidence of PA was 4% in the total population studied and 7.5% in the subgroup of hypertensive patients. In conclusion, the continuous enrollment of patients from the IPHAK+hypokalemia registry into the IPAHK+trial will provide evidence about the actual incidence of primary aldosteronism in a hypokalemic outpatient population.
Keywords: hypertension; endocrine hypertension; potassium; hypopotassemia